Climate change and income inequality: An empirical analysis - Haroon Mumtaz; Angeliki Theophilopoulou (Queen Mary University of London, School of Economics and Finance, 2023)
The role of climate change on economic performance and output has been studied extensively in the empirical literature, however, its distributional effects have received little attention. This paper attempts to fill this gap by investigating whether climate shocks affect income inequality in a large number of countries. We use data on climate indicators, income and inequality measures for 153 countries spanning a long time period. The climate shock is identified as the disturbance that explains the bulk of the climate fluctuations in the long run. Our findings suggest that an adverse climate shock is associated with an increase in measures of income inequality. We find a heterogeneous impact of the on the left and right tail within-country income distribution. The impact of the shock is larger in magnitude for low income and hot on average countries with a significant agricultural sector and low expenditure on health sector.
Keywords: C32; E32; Q54; 330; income inequality; economic growth; frequency domain identification; panel VAR